The Distinction Between Risk and Hazard: Understanding and Use in Stakeholder Communication. Issue 7 (20th January 2014) - Scheer, Dirk; Benighaus, Christina; Benighaus, Ludger; Renn, Ortwin; Gold, Stefan; Röder, Bettina; Böl, Gaby‐Fleur
<x xml:space="preserve">Abstract</x> A major issue in all risk communication efforts is the distinction between the terms "risk" and "hazard." The potential to harm a target such as human health or the environment is normally defined as a hazard, whereas risk also encompasses the probability of exposure and the extent of damage. What can be observed again and again in risk communication processes are misunderstandings and communication gaps related to these crucial terms. We asked a sample of 53 experts from public authorities, business and industry, and environmental and consumer organizations in Germany to outline their understanding and use of these terms using both the methods of expert interviews and focus groups. The empirical study made clear that the terms risk and hazard are perceived and used very differently in risk communication depending on the perspective of the stakeholders. Several factors can be identified, such as responsibility for hazard avoidance, economic interest, or a watchdog role. Thus, communication gaps can be reduced to a four‐fold problem matrix comprising a semantic, conceptual, strategic, and control problem. The empirical study made clear that risks and hazards are perceived very differently depending on the stakeholders' perspective. Their own worldviews played a major role in their specific use of the two terms hazards and risks in communication.